EARLY OUTCOMES OF MINIMALLY INVASIVE ESOPHAGECTOMY WITH GASTRIC TUBE RECONSTRUCTION FOR ESOPHAGEAL CANCER AT K HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the early outcomes of minimally invasive esophagectomy with gastric tube reconstruction for esophageal cancer at K Hospital.Methods: A retrospective descriptive study of 95 patients with esophageal cancer who underwent minimally invasive esophagectomy with gastric tube reconstruction at the Department of Gastrointestinal Surgery II, K Hospital, from January 2022 to December 2023.Results: The majority were male (98.9%), with a mean age of 57.1 ± 8.68 years (range 44–74). Tumors were located in the middle (47.4%) and lower (52.6%) thirds of the esophagus. Mean operative time was 298.9 ± 39.6 minutes. Mean lymph node yields were 15.9 ± 8.6 (thoracic) and 9.7 ± 3.8 (abdominal). Squamous cell carcinoma accounted for 90.5%. Intraoperative events occurred in 2 patients (2.1%). Mean hospital stay was 15.8 ± 6.35 days. Postoperative respiratory complications included pneumonia (6.3%), pleural effusion (2.1%), and atelectasis (1.1%). Anastomotic leak was recorded in 2.1% and anastomotic stenosis in 4.2%. No in-hospital or 30-day mortality was recorded.Conclusion: Minimally invasive esophagectomy with gastric tube reconstruction is a feasible procedure with an acceptable rate of early intraoperative and postoperative morbidity.
Keywords: esophageal cancer; minimally invasive surgery; esophagectomy; gastric tube; early complications